Pontiflex: A Brief Biographical Note on Some of the Contributions of Canon Eugene Fairweather to the Canadian Church - Baycroft, John (Toronto journal of theology, 1987)
How does theology serve the Church? What is the bridge between the institutional Church and the theological academy? For decades the Anglican Church of Canada has relied upon Canon Eugene Rathbone Fairweather of Trinity College to answer these questions, and to be himself the most distinguished example of the integration of the theological enterprise into the life of the faith community.